Halogen-free flame-retardant PC composite material with high recovery ratio
Through a high recovery ratio halogen-free flame-retardant PC composite material, combined with the combination of toughening agent, flame retardant and antioxidant, the existing PC composite material cannot take into account V-0 under high recovery ratio and ultra-thin thickness. The problem of flame retardant performance achieves flame retardant performance and environmentally friendly solutions under ultra-thin thickness.
Patent Information
- Application Number
- CN202310837854.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing PC composite materials cannot take into account V-0 flame retardant properties under high recycling ratio and ultra-thin thickness, which limits their application in harsh environments.
A halogen-free flame-retardant PC composite material with a high recovery ratio is used to form 97.0 to 98.6 parts by mass of PCR PC, 0 to 2.8 parts by mass of toughening agent, 0.1 to 2.9 parts by mass of halogen-free flame-retardant, 0.05 to 2 parts by mass of Parts of anti-drip agent and 0.05 to 2 parts of anti-oxidant are prepared by compounding and processing aids to achieve flame retardant properties under ultra-thin thickness.
Halogen-free flame-retardant PC composite material with high recycling ratio meets the V-0 flame retardant grade at ultra-thin thickness (≤0.8mm) and meets environmentally friendly standards, avoids secondary pollution and significantly improves the flame retardant effect. .
Smart Images

Figure BSA0000297159320000071
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of polycarbonate composite materials, in particular to a halogen-free flame-retardant PC composite material with a high recycling ratio. [Background technology]
[0002] Polycarbonate (PC, also known as PC resin) is an engineering plastic with excellent comprehensive properties (such as mechanical properties, dimensional stability, toughness, heat resistance, UV resistance and electrical properties). The flame retardant performance and grade of PC itself are UL94V-2. The three major application areas of its engineering plastics are glass assembly industry, automobile industry and electronics and electrical industry.
[0003] At present, with the vigorous promotion of mobile Internet in China and internationally, the characteristics of polymer materials that are different from other materials make their use in mobile Internet related devices increasingly large, and the excellent comprehensive performance of PC materials has also attracted close attention in mobile Internet. Now all walks of life at home and abroad are actively contributing to "carbon neutrality". PCR (Post-Consumer Recycled material) is one of the important directions to reduce plastic pollution and promote carbon neutrality. This method not only reduces carbon dioxide emissions, but also reduces energy consumption.
[0004] However, due to some treatments of PCR materials during the production process, such as crushing, secondary tube granulation, etc., its performance and stability will be reduced compared to the original material. At the same time, the UL94V-2 flame retardant performance level of PC itself limits its use in harsh environments, such as batteries, equipment and instruments in the new energy industry. After checking, there is currently a PCR content of 98% on the market, but its 0.8mm flame retardant is NG (Not Given, meaning poor process or poor product, used in production and manufacturing management). Compared with another one, its 0.8mm flame retardant is V-0, but the PCR content is only 90%. The information to be checked can be concluded: the industry's commercialized PC composite materials cannot take into account the V-0 flame retardant requirements under high PCR content (≥97%) and ultra-thin thickness (≤0.8mm).
[0005] In view of this, it is necessary to provide a halogen-free flame-retardant PC composite material with a high recycling rate to solve the above problems. [Summary of the invention]
[0006] The technical problem to be solved by the present invention is that the commercialized PC composite materials in the industry cannot meet the requirements of V-0 flame retardancy under high PCR content (≥97%) and ultra-thin thickness (≤0.8mm). Therefore, the present invention provides a halogen-free flame retardant PC composite material with a high recycling ratio to solve the above problem.
[0007] The solution of the present invention to solve the technical problem is:
[0008] A halogen-free flame-retardant PC composite material with a high recycling ratio, characterized in that it includes the following components in parts by weight:
[0009] PCR PC, 97.0-98.6 parts by mass;
[0010] Toughening agent, 0 to 2.8 parts by mass;
[0011] Flame retardant, 0.1 to 2.9 parts by mass;
[0012] Anti-dripping agent, 0.05 to 2 parts by mass;
[0013] Antioxidant, 0.05 to 2 parts by mass.
[0014] The high recovery ratio in the present invention refers to the content of PCR in the material being ≥ 97%.
[0015] The selected polycarbonate is a compound of one or more of bisphenol A polycarbonate, polyester polycarbonate, silicone copolymer PC, cyclohexane bisphenol A polycarbonate, and high-temperature resistant polycarbonate synthesized from bisphenol TMC. The melt mass flow rate MI of PC is between (5 and 70) g / 10 min (300° C. / 1.2 kg), the weight average molecular weight is between 20,000 and 50,000, and the molecular weight distribution is between 1 and 2.5.
[0016] The toughening agent selected can be a compound of one or more of unsaturated rubber, saturated rubber, styrene thermoplastic elastomer, polyurethane thermoplastic elastomer, polyolefin thermoplastic elastomer, polyamide thermoplastic elastomer, high rubber powder, acrylic copolymer (ACR), etc. and their derivatives.
[0017] The flame retardant selected can be a combination of one or more of hypophosphite flame retardants, phosphate flame retardants, sulfonate flame retardants, silicone flame retardants, etc. and their derivatives.
[0018] The selected anti-dripping agent is a fluorine-based PTFE material, including a core-shell coated PTFE material and a non-coated PTFE (pure powder type) material.
[0019] The antioxidant selected can be a combination of one or more of hindered phenols, phosphites, thio antioxidants, etc.
[0020] A product, characterized in that the product is prepared by using a processing aid to obtain a halogen-free flame-retardant PC composite material with a high recycling ratio.
[0021] The beneficial effect of the present invention is that the recycling sources of PCR PC used in the present invention are all daily production and life, such as drinking water bottles, optical discs, etc., and the processing methods are all physical. The process is to first physically recycle the waste plastics, then sort, grind, clean and granulate them in the recycling system, and finally make new plastic particles. The new plastic particles have the same structure as the plastic particles before recycling, and the new plastic particles can be used directly alone, or mixed with the original resin to create various new plastic products. In addition to the use of processing aids (toughening agents, flame retardants, anti-dripping agents, antioxidants) in this formulation, the remaining components are all PCR PC, and the flame retardants used in the present invention are all halogen-free flame retardants, which are environmentally friendly, meet and comply with national and international management and regulations, and will not cause secondary pollution to the environment. In addition, they have a small amount of addition and a significant effect of improving flame retardancy, and can achieve and meet the flame retardancy level under ultra-thin thickness (≤0.8mm). [Specific implementation method]
[0022] In order to further illustrate the technical means and effects adopted by the present invention, the embodiments of the present invention are described in detail below.
[0023] The present invention provides a halogen-free flame-retardant PC composite material with a high recycling ratio, comprising:
[0024] A halogen-free flame-retardant PC composite material with a high recycling ratio, characterized in that it includes the following components in parts by weight:
[0025] PCR PC, 97.0-98.6 parts by mass;
[0026] Toughening agent, 0 to 2.8 parts by mass;
[0027] Flame retardant, 0.1 to 2.9 parts by mass;
[0028] Anti-dripping agent, 0.05 to 2 parts by mass;
[0029] Antioxidant, 0.05 to 2 parts by mass.
[0030] The high recovery ratio in the present invention refers to the content of PCR in the material being ≥ 97%.
[0031] The ultra-thin halogen-free flame retardant mentioned in the present invention refers to the material being able to achieve flame retardant performance and fire rating requirements at an ultra-thin thickness (≤0.8mm) without adding halogen-containing flame retardants.
[0032] The selected polycarbonate is a compound of one or more of bisphenol A polycarbonate, polyester polycarbonate, silicone copolymer PC, cyclohexane bisphenol A polycarbonate, and high-temperature resistant polycarbonate synthesized from bisphenol TMC. The melt mass flow rate MI of PC is between (5 and 70) g / 10 min (300° C. / 1.2 kg), the weight average molecular weight is between 20,000 and 50,000, and the molecular weight distribution is between 1 and 2.5.
[0033] The toughening agent selected can be unsaturated rubber (such as nitrile rubber (NBR), natural rubber (NR), styrene-butadiene rubber (SBR), butadiene rubber (BR)), saturated rubber (such as butyl rubber (IIR), ethylene-propylene rubber (EPR), ethylene-propylene-diene rubber (EPDM), halogenated butyl rubber), styrene thermoplastic elastomer (such as methyl methacrylate-butadiene-styrene terpolymer (MBS), styrene-butadiene-styrene copolymer (SBS), hydrogenated SBS (SEBS), styrene-isoprene-styrene (SIS)), polyurethane thermoplastic elastomer (such as TPU), polyolefin thermoplastic elastomer (such as chlorinated polyethylene (CPE), ethylene-octene copolymer (POE), thermoplastic dynamic vulcanizate (TPV), ethylene-vinyl acetate copolymer (EVA)), polyamide thermoplastic elastomer (such as TPAE), high rubber powder, acrylic copolymer (ACR), etc. and their derivatives. One or more of the compounding and use.
[0034] The flame retardant selected can be a phosphite flame retardant (such as vinyl aluminum hypophosphite flame retardant, vinyl hypophosphite), a phosphate flame retardant (such as 1,3-phenylene phosphite (2,6-methylphenyl) tetraphosphate, tetraphenyl bisphenol A diphosphate and its derivative flame retardant (BDP), tetraphenyl resorcinol diphosphate and its derivative (RDP) flame retardant, triphenyl phosphate (TPP) flame retardant), a sulfonate flame retardant (such as potassium benzenesulfonylbenzenesulfonate (KSS), potassium perfluorobutyl sulfonate (PPFBS), sodium 2,4,5-trichlorobenzenesulfonate (STB)), an organosilicon flame retardant (such as polysilborane and its derivative flame retardant, cross-linked polydimethylsiloxane (PDMS)), etc. and their derivatives. One or more of the compounding and use.
[0035] The selected anti-dripping agent is a fluorine-based PTFE material, including a core-shell coated PTFE material and a non-coated PTFE (pure powder type) material.
[0036] The antioxidant selected can be a combination of one or more of hindered phenols (such as (β-3,5-di-tert-butyl-4-hydroxyphenyl) octadecyl acrylate), phosphites (such as tris(2,4-di-tert-butylphenyl) phosphite, dioctadecyl alcohol pentaerythritol diphosphite), thio antioxidants, etc.
[0037] Example 1
[0038] A halogen-free flame-retardant PC composite material with a high recycling ratio comprises the following components in parts by weight: 40 parts of PCR PC-1, 58.6 parts of PCR PC-2, 0 parts of a toughening agent, 0.1 parts of a sulfonate flame retardant-1, 0.3 parts of a sulfonate flame retardant-2, 0.4 parts of a silicone flame retardant, 0.3 parts of an anti-dripping agent, and 0.3 parts of an antioxidant.
[0039] Among them, the two types of PCR PC selected are both bisphenol A linear polycarbonate, synthesized by phosgene method, and their MI are MI (PCR PC-1) = 65g / 10min (300℃ / 1.2kg) and MI (PCR PC-2) = 6.5g / 10min (300℃ / 1.2kg), respectively, and the weight average molecular weights are between 25000 and 30000 and 49000 and 50000, respectively, and the molecular weight distribution is between 1.5 and 2.0.
[0040] Among them, the toughening agent selected is styrene-based thermoplastic elastomer MBS, which can significantly improve the impact resistance of resins and engineering plastics, and at the same time has excellent heat aging resistance and hydrolysis resistance.
[0041] Among them, the compound of sulfonate flame retardant and silicone flame retardant is selected, which has the advantages of small addition amount and can achieve flame retardant requirements and fire protection level in ultra-thin thickness (≤0.8mm).
[0042] Among them, the anti-drip agent selected is non-coated PTFE (pure powder type), which has the advantages of small addition amount, significant anti-drip effect, and can effectively improve the flame retardant problem.
[0043] Among them, the antioxidant selected is a compound of hindered phenols and phosphites, which has a significant synergistic effect and has the characteristics of small addition amount and significant antioxidant and anti-yellowing effects.
[0044] The processing machine used is a twin-screw extruder, and the processing temperature is 280-290°C.
[0045] When preparing the halogen-free flame-retardant PC composite material with a high recycling ratio, the components in corresponding weight parts are weighed according to the above ratio, and the components are evenly mixed and then melt-extruded and granulated.
[0046] Example 2
[0047] A halogen-free flame-retardant PC composite material with a high recycling ratio comprises the following components in parts by weight: 40 parts of PCR PC-1, 58.1 parts of PCR PC-2, 0.5 parts of a toughening agent, 0.1 parts of a sulfonate flame retardant-1, 0.3 parts of a sulfonate flame retardant-2, 0.4 parts of a silicone flame retardant, 0.3 parts of an anti-dripping agent, and 0.3 parts of an antioxidant.
[0048] Among them, the two types of PCR PC selected are both bisphenol A linear polycarbonate, synthesized by phosgene method, and their MI are MI (PCR PC-1) = 65g / 10min (300℃ / 1.2kg) and MI (PCR PC-2) = 6.5g / 10min (300℃ / 1.2kg), respectively, and the weight average molecular weights are between 25000 and 30000 and 49000 and 50000, respectively, and the molecular weight distribution is between 1.5 and 2.0.
[0049] Among them, the toughening agent selected is styrene-based thermoplastic elastomer MBS, which can significantly improve the impact resistance of resins and engineering plastics, and at the same time has excellent heat aging resistance and hydrolysis resistance.
[0050] Among them, the compound of sulfonate flame retardant and silicone flame retardant is selected, which has the advantages of small addition amount and can achieve flame retardant requirements and fire protection level in ultra-thin thickness (≤0.8mm).
[0051] Among them, the anti-drip agent selected is non-coated PTFE (pure powder type), which has the advantages of small addition amount, significant anti-drip effect, and can effectively improve the flame retardant problem.
[0052] Among them, the antioxidant selected is a compound of hindered phenols and phosphites, which has a significant synergistic effect and has the characteristics of small addition amount and significant antioxidant and anti-yellowing effects.
[0053] The processing machine used is a twin-screw extruder, and the processing temperature is 280-290°C.
[0054] When preparing the halogen-free flame-retardant PC composite material with a high recycling ratio, the components in corresponding weight parts are weighed according to the above ratio, and the components are evenly mixed and then melt-extruded and granulated.
[0055] Example 3
[0056] A halogen-free flame-retardant PC composite material with a high recycling ratio comprises the following components in parts by weight: 40 parts of PCR PC-1, 57.6 parts of PCR PC-2, 1 part of a toughening agent, 0.1 parts of a sulfonate flame retardant-1, 0.3 parts of a sulfonate flame retardant-2, 0.4 parts of a silicone flame retardant, 0.3 parts of an anti-dripping agent, and 0.3 parts of an antioxidant.
[0057] Among them, the two types of PCR PC selected are both bisphenol A linear polycarbonate, synthesized by phosgene method, and their MI are MI (PCR PC-1) = 65g / 10min (300℃ / 1.2kg) and MI (PCR PC-2) = 6.5g / 10min (300℃ / 1.2kg), respectively, and the weight average molecular weights are between 25000 and 30000 and 49000 and 50000, respectively, and the molecular weight distribution is between 1.5 and 2.0.
[0058] Among them, the toughening agent selected is styrene-based thermoplastic elastomer MBS, which can significantly improve the impact resistance of resins and engineering plastics, and at the same time has excellent heat aging resistance and hydrolysis resistance.
[0059] Among them, the compound of sulfonate flame retardant and silicone flame retardant is selected, which has the advantages of small addition amount and can achieve flame retardant requirements and fire protection level in ultra-thin thickness (≤0.8mm).
[0060] Among them, the anti-drip agent selected is non-coated PTFE (pure powder type), which has the advantages of small addition amount, significant anti-drip effect, and can effectively improve the flame retardant problem.
[0061] Among them, the antioxidant selected is a compound of hindered phenols and phosphites, which has a significant synergistic effect and has the characteristics of small addition amount and significant antioxidant and anti-yellowing effects.
[0062] The processing machine used is a twin-screw extruder, and the processing temperature is 280-290°C.
[0063] When preparing the halogen-free flame-retardant PC composite material with a high recycling ratio, the components in corresponding weight parts are weighed according to the above ratio, and the components are evenly mixed and then melt-extruded and granulated.
[0064] Example 4
[0065] A halogen-free flame-retardant PC composite material with a high recycling ratio comprises the following components in parts by weight: 40 parts of PCR PC-1, 57.1 parts of PCR PC-2, 1.5 parts of a toughening agent, 0.1 parts of a sulfonate flame retardant-1, 0.3 parts of a sulfonate flame retardant-2, 0.4 parts of a silicone flame retardant, 0.3 parts of an anti-dripping agent, and 0.3 parts of an antioxidant.
[0066] Among them, the two types of PCR PC selected are both bisphenol A linear polycarbonate, synthesized by phosgene method, and their MI are MI (PCR PC-1) = 65g / 10min (300℃ / 1.2kg) and MI (PCR PC-2) = 6.5g / 10min (300℃ / 1.2kg), respectively, and the weight average molecular weights are between 25000 and 30000 and 49000 and 50000, respectively, and the molecular weight distribution is between 1.5 and 2.0.
[0067] Among them, the toughening agent selected is styrene-based thermoplastic elastomer MBS, which can significantly improve the impact resistance of resins and engineering plastics, and at the same time has excellent heat aging resistance and hydrolysis resistance.
[0068] Among them, the compound of sulfonate flame retardant and silicone flame retardant is selected, which has the advantages of small addition amount and can achieve flame retardant requirements and fire protection level in ultra-thin thickness (≤0.8mm).
[0069] Among them, the anti-drip agent selected is non-coated PTFE (pure powder type), which has the advantages of small addition amount, significant anti-drip effect, and can effectively improve the flame retardant problem.
[0070] Among them, the antioxidant selected is a compound of hindered phenols and phosphites, which has a significant synergistic effect and has the characteristics of small addition amount and significant antioxidant and anti-yellowing effects.
[0071] The processing machine used is a twin-screw extruder, and the processing temperature is 280-290°C.
[0072] When preparing the halogen-free flame-retardant PC composite material with a high recycling ratio, the components in corresponding weight parts are weighed according to the above ratio, and the components are evenly mixed and then melt-extruded and granulated.
[0073] Example 5
[0074] A halogen-free flame-retardant PC composite material with a high recycling ratio comprises the following components in parts by weight: 60 parts of PCR PC-1, 37.6 parts of PCR PC-2, 1 part of a toughening agent, 0.1 parts of a sulfonate flame retardant-1, 0.3 parts of a sulfonate flame retardant-2, 0.4 parts of a silicone flame retardant, 0.3 parts of an anti-dripping agent, and 0.3 parts of an antioxidant.
[0075] Among them, the two types of PCR PC selected are both bisphenol A linear polycarbonate, synthesized by phosgene method, and their MI are MI (PCR PC-1) = 65g / 10min (300℃ / 1.2kg) and MI (PCR PC-2) = 6.5g / 10min (300℃ / 1.2kg), respectively, and the weight average molecular weights are between 25000 and 30000 and 49000 and 50000, respectively, and the molecular weight distribution is between 1.5 and 2.0.
[0076] Among them, the toughening agent selected is styrene-based thermoplastic elastomer MBS, which can significantly improve the impact resistance of resins and engineering plastics, and at the same time has excellent heat aging resistance and hydrolysis resistance.
[0077] Among them, the compound of sulfonate flame retardant and silicone flame retardant is selected, which has the advantages of small addition amount and can achieve flame retardant requirements and fire protection level in ultra-thin thickness (≤0.8mm).
[0078] Among them, the anti-drip agent selected is non-coated PTFE (pure powder type), which has the advantages of small addition amount, significant anti-drip effect, and can effectively improve the flame retardant problem.
[0079] Among them, the antioxidant selected is a compound of hindered phenols and phosphites, which has a significant synergistic effect and has the characteristics of small addition amount and significant antioxidant and anti-yellowing effects.
[0080] The processing machine used is a twin-screw extruder, and the processing temperature is 280-290°C.
[0081] When preparing the halogen-free flame-retardant PC composite material with a high recycling ratio, the components in corresponding weight parts are weighed according to the above ratio, and the components are evenly mixed and then melt-extruded and granulated.
[0082] Example 6
[0083] A halogen-free flame-retardant PC composite material with a high recycling ratio comprises the following components in parts by weight: 60 parts of PCR PC-1, 37.1 parts of PCR PC-2, 1.5 parts of a toughening agent, 0.1 parts of a sulfonate flame retardant-1, 0.3 parts of a sulfonate flame retardant-2, 0.4 parts of a silicone flame retardant, 0.3 parts of an anti-dripping agent, and 0.3 parts of an antioxidant.
[0084] Among them, the two types of PCR PC selected are both bisphenol A linear polycarbonate, synthesized by phosgene method, and their MI are MI (PCR PC-1) = 65g / 10min (300℃ / 1.2kg) and MI (PCR PC-2) = 6.5g / 10min (300℃ / 1.2kg), respectively, and the weight average molecular weights are between 25000 and 30000 and 49000 and 50000, respectively, and the molecular weight distribution is between 1.5 and 2.0.
[0085] Among them, the toughening agent selected is styrene-based thermoplastic elastomer MBS, which can significantly improve the impact resistance of resins and engineering plastics, and at the same time has excellent heat aging resistance and hydrolysis resistance.
[0086] Among them, the compound of sulfonate flame retardant and silicone flame retardant is selected, which has the advantages of small addition amount and can achieve flame retardant requirements and fire protection level in ultra-thin thickness (≤0.8mm).
[0087] Among them, the anti-drip agent selected is non-coated PTFE (pure powder type), which has the advantages of small addition amount, significant anti-drip effect, and can effectively improve the flame retardant problem.
[0088] Among them, the antioxidant selected is a compound of hindered phenols and phosphites, which has a significant synergistic effect and has the characteristics of small addition amount and significant antioxidant and anti-yellowing effects.
[0089] The processing machine used is a twin-screw extruder, and the processing temperature is 280-290°C.
[0090] When preparing the halogen-free flame-retardant PC composite material with a high recycling ratio, the components in corresponding weight parts are weighed according to the above ratio, and the components are evenly mixed and then melt-extruded and granulated.
[0091] After the above embodiments are implemented, they are reproduced according to the same components, and the embodiments 1, 2,
[0092] After melt extrusion granulation of Example 3, Example 4, Example 5 and Example 6, the particles in each example were injection molded into standard test specimens on an injection molding machine, and the mechanical properties of the obtained materials were tested according to the standard. The test results are shown in Table 1:
[0093] Table 1 Test results
[0094]
[0095] From the test results of Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6, it can be seen that the present invention uses processing aids to achieve the preparation of a halogen-free flame-retardant PC composite material with a high recovery ratio.
[0096] The beneficial effect of the present invention is that the recycling sources of PCR PC used in the present invention are all daily production and life, such as drinking water bottles, optical discs, etc., and the processing methods are all physical. The process is to first physically recycle the waste plastics, then sort, grind, clean and granulate them in the recycling system, and finally make new plastic particles. The new plastic particles have the same structure as the plastic particles before recycling, and the new plastic particles can be used directly alone, or mixed with the original resin to create various new plastic products. In addition to the use of processing aids (toughening agents, flame retardants, anti-dripping agents, antioxidants) in this formulation, the remaining components are all PCR PC, and the flame retardants used in the present invention are all halogen-free flame retardants, which are environmentally friendly, meet and comply with national and international management and regulations, and will not cause secondary pollution to the environment. In addition, they have a small amount of addition and a significant effect of improving flame retardancy, and can achieve and meet the flame retardancy level under ultra-thin thickness (≤0.8mm).
[0097] It should be pointed out that the present invention is not limited to the above-mentioned implementation modes, and any simple modifications, equivalent changes and modifications made to the above-mentioned embodiments by any technician familiar with the profession based on the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A halogen-free flame-retardant PC composite material with a high recycling ratio, characterized in that: The composition comprises the following components in parts by weight: PCR PC, 97.0-98.6 parts by mass; Toughening agent, 0 to 2.8 parts by mass; Flame retardant, 0.1 to 2.9 parts by mass; Anti-dripping agent, 0.05 to 2 parts by mass; Antioxidant, 0.05 to 2 parts by mass.
2. The halogen-free flame-retardant PC composite material with a high recycling ratio as claimed in claim 1, characterized in that: The selected polycarbonate is a compound of one or more of bisphenol A polycarbonate, polyester polycarbonate, silicone copolymer PC, cyclohexane bisphenol A polycarbonate, and high-temperature resistant polycarbonate synthesized from bisphenol TMC. The melt mass flow rate MI of PC is between (5 and 70) g / 10 min (300° C. / 1.2 kg), the weight average molecular weight is between 20,000 and 50,000, and the molecular weight distribution is between 1 and 2.
5.
3. The halogen-free flame-retardant PC composite material with a high recycling ratio as claimed in claim 1, characterized in that: The toughening agent selected can be a compound of one or more of unsaturated rubber, saturated rubber, styrene thermoplastic elastomer, polyurethane thermoplastic elastomer, polyolefin thermoplastic elastomer, polyamide thermoplastic elastomer, high rubber powder, acrylic copolymer (ACR), etc. and their derivatives.
4. The halogen-free flame-retardant PC composite material with a high recycling ratio as claimed in claim 1, characterized in that: The flame retardant selected can be a combination of one or more of hypophosphite flame retardants, phosphate flame retardants, sulfonate flame retardants, silicone flame retardants, etc. and their derivatives.
5. The halogen-free flame-retardant PC composite material with a high recycling ratio as claimed in claim 1, characterized in that: The selected anti-dripping agent is a fluorine-based PTFE material, including a core-shell coated PTFE material and a non-coated PTFE (pure powder type) material.
6. The halogen-free flame-retardant PC composite material with a high recycling ratio as claimed in claim 1, characterized in that: The antioxidant selected can be a combination of one or more of hindered phenols, phosphites, thio antioxidants, etc.
7. The halogen-free flame-retardant PC composite material with a high recycling ratio as claimed in claim 1, characterized in that: The processing machine selected is a twin-screw extruder, and the processing temperature is 280-290°C.